EVALUASI PELAKSANAAN PEMBANGUNAN RUANG KELAS BARU SMK NEGERI 1 TUNJUNG TEJA DENGAN EARNED VALUE ANALISYS (Journal of Sustainable Civil Engineering (JOSCE), 2024)
In running a construction project, good management is needed so that the work is carried out on time. Project success is strongly influenced by cost, quality, and time factors. Two important factors that must be considered are cost and time. Project control can be done by applying the Earned Value Analysis method to both aspects. This study aims to evaluate the implementation of the construction of new classrooms at SMK Negeri 1 Tunjungteja. This evaluation is important to assess the extent to which the project is running according to plan in terms of cost, time, and results achieved. EVA methodology was applied to measure project performance. Data was collected from project reports, work schedules, and budgets that had been prepared where the data used was data for the period from week 1 to week 21. The results showed that in week 1 to 21 the SV value was known to be the highest ratio in the week 13 period. Then the SV value in the 1st period to the 21st period found a negative value. For the SPI value, it has a value